Bahasa lisan pada anak usia 4 tahun dengan keterlambatan bicara (speech delay) - Halimah, Halimah; Jumriah, Jumriah; Susilo, Susilo (Universitas Mulawarman, 2024)
This study aims to describe the speech delay of a 4-year-old child with speech delay, identified as A. This study analyzes the child's spoken language processes and the causes of the speech delay. The researcher used a descriptive qualitative method with a single-subject research technique. Data were collected using observation and interview techniques with informants, namely A, A's parents, and teachers at school. Based on the analysis, the following findings were observed: (1) the accuracy of speech in some consonant sounds has changed, specifically the articulation of consonant sounds /m, p, b/ to consonant sounds /h/; (2) the placement of stress, tone, coding, and duration is appropriate, but the stress in speaking sometimes causes the child to lower or raise the intonation of word sounds in certain circumstances; (3) the choice of words is less varied; and (4) the conversation is on target when focused. The factors that contribute to A's speech delay are genetic factors from one of the family members and environmental factors. When A was experiencing language acquisition, there was a lockdown due to Covid-19, which resulted in limited interaction and less stimulation from close individuals and the environment where he lived.